2004
DOI: 10.1002/pd.794
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of mosaic distal 5p deletion and review of the literature

Abstract: The cri-du-chat syndrome can be identified prenatally because of advanced maternal age, familial cri-du-chat syndrome, parental balanced translocations involving chromosome 5, sonographically detected fetal structural abnormalities, and/or an abnormal maternal serum test. Fetuses with the mosaic distal 5p deletion may be associated with the sonographic findings of microcephaly and cerebellar hypoplasia, and fetoplacental and fetoamnionic chromosomal discrepancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…The high-arched palate that we observed in this case was also described in another case by Guć-Sćekić et al (1989). Facial dysmorphism and camptodactyly in our case was observed by Chen et al (2004) in a patient with the karyotype 46,XX, del(11)(q24.1). It is difficult to define a distinctive phenotype in 11q partial monosomy as the phenotype depends on haploinsufficient genes.…”
Section: Discussionsupporting
confidence: 60%
“…The high-arched palate that we observed in this case was also described in another case by Guć-Sćekić et al (1989). Facial dysmorphism and camptodactyly in our case was observed by Chen et al (2004) in a patient with the karyotype 46,XX, del(11)(q24.1). It is difficult to define a distinctive phenotype in 11q partial monosomy as the phenotype depends on haploinsufficient genes.…”
Section: Discussionsupporting
confidence: 60%
“…According to our observation of the prenatal phenotype in 11qter deletion cases, hyperechogenic bowel should be appended to the previously described features: Thickening of the NT [McClelland et al, 1998], growth retardation, and shortening of the femurs and humeri [Wax et al, 1995;Chen et al, 2002;Chen et al, 2004]. Moreover, our data show that the size of the deletion is not critical for the severity of the phenotype.…”
Section: Discussionmentioning
confidence: 47%
“…The expansion of array technologies in the last few years has permitted the precise characterization of the deletions and detailed genotype/phenotype correlations in postnatal cases of JBS. [Penny et al, 1995;Wax et al, 1995;Chen et al, 1997;McClelland et al, 1998;Porter et al, 1999;Chen et al, 2002;Favier et al, 2003;Chen et al, 2004;Grossfeld et al, 2004;Boehm et al, 2006] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We nonetheless observed 26 abnormal karyotypes among the 223 fetuses with this isolated marker. In a review of the literature, Chen et al [13] showed that increased nuchal translucency may be a sonographic manifestation of some uncommon numerical aneuploidies and also a first-trimester feature of some uncommon structural aneuploidies [14] .…”
Section: Minor Anomaliesmentioning
confidence: 99%